Sistem Pakar Berbasis Web Untuk Diagnosa Hama Dan Penyakit Jamur Tiram Pada Kelompok Tani Desa Dasan Borok Kabupaten Lombok Timur - nur ida nurhidayati; Aris Sudianto; Suhartini Suhartini (Fakultas Teknik Universitas Hamzanwadi, 2020)
The application and use of technology today has been seen in almost every field of human life. This technology is here to help and facilitate humans in completing work and overcoming a variety of complex problems even for example in terms of analyzing as happened to the farmers and groups of oyster mushroom entrepreneurs in Dasan Borok Village, Suralaga District, East Lombok. The frequent occurrence of crop failure is a problem that currently occurs every time the harvest comes, this occurrence causes losses to farmers and must be dealt with quickly and appropriately. Web-based expert system is the right solution to overcome these problems, where this system can become an information center and be used as a tool in making decisions for farmers and entrepreneurs of oyster mushrooms to be able to determine the cause of damage and detect the types of diseases and pests that attack oyster mushrooms. With the implementation of this system it is expected to be able to overcome or reduce the problems of farmers to improve better and maximum yields.DOI : 10.29408/jit.v3i2.2316